Comparison of Phenotypic and DNA Variation Between Males and Females of Red and Black-Eyed Albino Lovebirds - Dr. Mudawamah; Muhammad Rifky Yuwanto; Sunaryo (UNIVERSITAS ISLAM LAMONGAN, 2024)
This research was conducted at the Bambang Iswanto Lovebird house regency Malang and the UNISMA Halal Center Laboratory. This study aimed to measure phenotype variation and DNA of male and female Lovebird Albino with a red and black eyes. The material in this study was 40 Lovebird Albino red eyes and black eyes with male sex (MHJ) and female sex (MHB). The experimental design used descriptive quantitative. The research variables followed wing length, chest size, body length and qPCR DNA with gen TYR. The data were analyzed using a T-test unpaired. The phenotype variation in wing length, chest size, and body length between male and female Lovebird Albino red eye showed no significant effect (P>0,05). The average value on wing length was 13,7 ± 1,89 cm (MMJ), 13,2 ± 1,48 cm (MHJ), 13,7 ± 1,31 cm (MMB), 13,2 ± 2,16 cm (MHB). The average value on chest size was 6,5 ± 1,89 cm (MMJ), 6,5 ± 1,48 cm (MHJ), 6,5 ± 0,53 cm (MMB), 6,5 ± 0,53 cm (MHB). The average value for body length was 15,40 ± 0,97 cm (MMJ), 15,20 ± 0,79 cm (MHJ), 15,20 ± 0,79 cm (MMB), 15,20 ± 0,63 cm (MHB). Average values on qPCR DNA were 37,67 ± 1,79 (MMJ), 35,22 ± 3,66 (MHJ), 37,90 ± 2,12 (MMB) and 35,89 ± 2,99 (MHB). The conclusion was phenotype variation and DNA Lovebird Albino red and black eyes on males and females has no significant effect but have propensity Lovebird Albino red eyes both in male and female higher 3,79% until 6,96% compared to black eye seen from wing length and DNA.